Kinetics of carbide formation in the molybdenum–tungsten coatings used in the ITER-like Wall. (21st January 2016) - Maier, H; Rasinski, M; von Toussaint, U; Greuner, H; Böswirth, B; Balden, M; Elgeti, S; Ruset, C; Matthews, G F
Abstract: The kinetics of tungsten carbide formation was investigated for tungsten coatings on carbon fibre composite with a molybdenum interlayer as they are used in the ITER-like Wall in JET. The coatings were produced by combined magnetron sputtering and ion implantation. The investigation was performed by preparing focused ion beam cross sections from samples after heat treatment in argon atmosphere. Baking of the samples was done at temperatures of 1100 °C, 1200 °C, and 1350 °C for hold times between 30 min and 20 h. It was found that the data can be well described by a diffusional random walk with a thermally activated diffusion process. The activation energy was determined to be (3.34 ± 0.11) eV. Predictions for the isothermal lifetime of this coating system were computed from this information.